Negative first follow‐up prostate biopsy on active surveillance is associated with decreased risk of upgrading, suspicion of progression and converting to active treatment. (15th November 2020) - Singh, Sohail; Sandhu, Preeti; Beckmann, Kerri; Santaolalla, Aida; Dewan, Kamal; Clovis, Sharon; Rusere, Jonah; Zisengwe, Grace; Challacombe, Benjamin; Brown, Christian; Cathcart, Paul; Popert, Rick; et al.
Abstract : Objective: To determine the risk of disease progression and conversion to active treatment following a negative biopsy while on active surveillance (AS) for prostate cancer (PCa). Patients and Methods: Men on an AS programme at a single tertiary hospital (London, UK) between 2003 and 2018 with confirmed low–intermediate‐risk PCa, Gleason Grade Group <3, clinical stage <T3 and a diagnostic prostate‐specific antigen (PSA) level of <20 ng/mL. This cohort included men diagnosed by transrectal ultrasonography guided (12–14 cores) or transperineal (median 32 cores) biopsy. Multivariate Cox hazards regression analysis was undertaken to determine (i) risk of upgrading, (ii) clinical or radiological suspicion of disease progression, and (iii) transitioning to active treatment. Suspicion of disease progression was defined as any biopsy upgrading, >30% positive cores, magnetic resonance imaging (MRI) Likert score >3/T3 or PSA level of >20 ng/mL. Conversion to treatment included radical or hormonal treatment. Results: Among the 460 eligible patients, 23% had negative follow‐up biopsy findings. The median follow‐up was 62 months, with one to two repeat biopsies and two MRIs per patient during that period. Negative biopsy findings at first repeat biopsy were associated with decreased risk of converting to active treatment (hazard ration [HR] 0.18, 95% confidence interval [CI] 0.09–0.37; P  < 0.001), suspicion of disease progression (HR 0.56, 95% CI: 0.34–0.94; P  = 0.029), and upgrading (HR 0.48, 95% CI 0.23–0.99; P  = 0.047). Data are limited by fewer men with multiple follow‐up biopsies. Conclusion: A negative biopsy finding at the first scheduled follow‐up biopsy among men on AS for PCa was strongly associated with decreased risk of subsequent upgrading, clinical or radiological suspicion of disease progression, and conversion to active treatment. A less intense surveillance protocol should be considered for this cohort of patients.